Women, Men and Gender Equality in Development Aid – Trajectories, Contestations - Arnfred, Signe (Kvinder, Køn & Forskning, 2011)
Women, men and gender equality in development aid - trajectories, contestations. The Beijing Platform for Action introduced notions of gender equality, which have been picked up by donors and development agents in increasingly popular images of strong enterprising women, however with an emphasis on economic entrepreneurship, disregarding aspects of care- and motherwork. At the same time ‘colonial feminism’ is still around, with its notions of women in the global South as oppressed under ‘tradition’ but rescued by development and ‘modernity’. Such images have been re-invigorated in the global War on Terror, from 2001 onwards. The article investigates implications of these different but co-existing images of women in development contexts. It also discusses limitations of notions of gender equality, when used by donors and by women’s organizations, and when discussed and critizised by post-colonial feminists.